Effect of titanate coupling agent on antioxidant property and UV blocking property of PBAT/lignin composite films - Honghuan Li; Jianping Ding; Yelzati Aytibeke; Liupeizhi Yuan; Yitong Jiang; Mamatjan Yimit (Polymer Testing)
PBAT is the largest amount of biomass-degradable plastics on the market at present, and its application in related fields is limited due to its defects such as poor weather resistance. In this study, the surface modification of lignin by titanate coupling agent was realized by the melt extrusion reaction method of non-catalytic system, and the PBAT/cotton straw lignin composite film was prepared by melt blending and blow molding with PBAT at a certain ratio. The structure and properties of the specimens were analyzed before and after the artificial accelerated aging test using characterization means such as DSC, SEM, IR, transmittance and mechanical properties. The results showed that the tensile strength and elongation at break ratios of the composite film increased by 36.99 % and 34.31 %, respectively, compared with the pure PBAT film when the titanate coupling agent modified lignin was 10 %; the retained value of elongation at break of the specimen on the sixth day of thermo-oxidative light aging increased by 13.33 %; and the UV transmittance at 500 nm was reduced by 96.95 %; And through the comprehensive evaluation system of material stability, the temperature aging kinetic model was established and a temperature sensitivity analysis was performed, and it was found that the specimen with 10 % lignin content had a significant reduction in temperature sensitivity. The composite film developed in this study maintains the fully biodegradable properties of PBAT while introducing the characteristics of functional modifiers, which provides a new idea to broaden the application in the field of packaging and helps to reduce the production cost.